Quantitative assessment of tricuspid regurgitation using pulsed Doppler echocardiography. Issue 5 (November 1983) - Diebold, B; Touati, R; Blanchard, D; Colonna, G; Guermonprez, J L; Peronneau, P; Forman, J; Maurice, P
Abstract : Tricuspid valve regurgitation was assessed quantitatively by measuring blood flow velocity in the vena cava using a pulsed Doppler velocimeter. A non-invasive index of regurgitation was obtained by calculating the ratio between the maximum amplitudes of the systolic and diastolic components of the velocity curves. The index was compared with the angiographic grading of regurgitation in 70 patients after right heart catheterisation; the results were closely correlated. Using the Doppler index the differences between the groups defined according to their angiographic grade were significant. Thus measurement of blood flow velocity in the vena cava appears to quantify accurately the severity of tricuspid regurgitation.